Determinants that influence the movement of housing price in Malaysia / Muhammad Fakhri Mohamad Zukri - Mohamad Zukri, Muhammad Fakhri (Faculty of Business and Management, 2018)
This study examines the relationships that between housing price in Malaysia (HPI) and the determinants of base lending rate (BLR), inflation rate (CPI), money supply (FD) and economic growth (GDP) from the year of 2005 to 2016 which contains annual data. This paper applies Auto-Regressive Distributed Lag (ARDL) Model in order to define the statistical relationship among the variables. Besides, there are steps involved in the study begin with this method and proceed with Bound Test, Diagnostic Checking, Unit Root tests, and Cointegration Test. In Diagnostic Checking, some tests done to check the significant presents of autocorrelation, heteroscedasticity, the normality of data distribution and model specification. The result of this study show that there is a significant relationship between the housing price (HPI) and base lending rate (BLR), money supply (FD) and economic growth (GDP), while inflation rate (CPI) did not have any significant relationship with the HPI. The recommendation for the future studies is future studies should use other factors instead of macroeconomics factor in order to examine the factors that affecting the housing price movement in Malaysia. The conclusion for the studies shows that the BLR, FD and GDP become the factors that affecting the HPI in Malaysia.